LABORATORY DIAGNOSTICS OF GENETIC PREDICTORS OF HOMOCYSTEINE IN THE DEVELOPMENT OF MIGRAINE - Kambarova, Dildora; Usmanova, Durdona (Medical science of Uzbekistan, 2023)
The article studied various options for the development of the pathogenesis of migraine. In addition to the aforementioned pathogenesis, another homocysteine-related migraine hypothesis has emerged, i.e. elevated homocysteine ​​concentration reduces glutathione production with subsequent oxidative stress and oxidation of homocysteine.